The Clinical Experiences of Urine Metabolomics of Genitourinary Urothelial Cancer in a Tertiary Hospital in Taiwan - Juang, Horng-Heng; Chen, Shao-Ming; Lin, Gigin; Chiang, Meng-Han; Hou, Chen-Pang; Lin, Yu-Hsiang; Yang, Pei-Shan; Chang, Phei-Lang; Chen, Chien-lun; Lin, Kuo-Yen; Tsui, Ke-Hung (Frontiers in Oncology, 2021)
There are only a few studies have addressed the impact of diagnostic urine metabolites and clinical outcomes associated with genitourinaryurothelial(GU)cancer up till this date.Furthermore, the longitudinal analysis of the dynamics of urine metabolites contributing to the detection of GUcancer has not yet been fully investigated;therefore, the discovery of novel diagnostic urine biomarkers is of our enormous interest. We explored the correlation of the urine metabolomics profiles to the GU cancers. The aqueous metabolites of the GU cancerand thecontrol were also identified and analyzed through high-resolution1H nuclear magnetic resonance (NMR) spectroscopy. Compared with the control, the urine metabolites of the tumor were studied in relation to changes over time in a linear mixed model for repeated measures.The urine metabolomof eighty-two (58 males and 24 female) patients with GU cancersweresystemically analyzed.The urine metabolite profile in GU cancer was significantly higher than those in the control group (p<0.05). Sevenurine metabolitesincludinghistidine, propylene glycol, valine, leucine, acetylsalicylate, glycine and isoleucineas well asother pathways were identifiedstatistically significantly associated with GU cancer detection with longitudinal analysis.We discovered that histidine, propylene glycol, valine, leucine, acetylsalicylate, glycine, isoleucine, succinic acid, lysine2-aminobutyric acid and acetic acid are involved significantly in the all types of the male patients. We did not findanystatistically significanceinurine biomarkers between female and male patients.However, a statistically insignificantcorrelation was found among the grade and stage with the metabolites.The urine metabolomic profiles of the GU tumors and the control group are distinct. The urine metabolites of the male patients of the upper tract urothelialcarcinoma(UTUC) were found statistically significance compared with the control.